Helicity‐Dependent Multifunctional Metasurfaces for Full‐Space Wave Control. Issue 8 (20th February 2020) - Zhang, Chiben; Wang, Guangming; Xu, He‐Xiu; Zhang, Xin; Li, Hai‐Peng
Abstract: Full‐space manipulation of electromagnetic waves with a thin flat plate is particularly intriguing for large‐angle scanning, functionality integration, and data capacity applications. However, majority of the designs to date are confined to linearly‐polarized wave operations; these render the versatile full‐space device operating under circularly‐polarized waves unaddressed due to the critical issue of the geometric phase being hardly decoupled among reflections and transmissions. Herein, a strategy for a helicity‐dependent multifunctional design by sandwiching dual‐layer geometric phase metasurfaces with a bandpass frequency selective surface is reported. The top and bottom metasurfaces are composed of two different types of meta‐structures, split ring resonators (SRRs) and a modified H‐shaped structure, which enable triple‐independent wavefronts at lower and upper frequencies ( f 1 and f 2 ). At f 1, the top and bottom SRRs operate under reflection mode on both sides, and two distinctive wavefronts can be modulated by individually rotating the orientations of SRRs. However, at f 2, the modified H‐shaped structure operates in transmission geometry, and additional functionality can be independently modulated by changing their orientations. As a proof of concept, a multifunctional meta‐device is constructed with triple‐versatile functionalities. The approach followed in this study sets up a solid platform for arbitrary helicity‐dependent full‐space integrated devices. Abstract : Triple functionalities ( F 1, F 2, F 3 ) of proposed helicity‐dependent full‐space metasurfaces are performed in transmission and reflection modes. Split ring resonators (SRRs) operate under reflection mode on both sides, and two distinctive wavefronts can be modulated by individually rotating the orientations of SRRs. However, the modified H‐shaped structure operates under transmission mode, and additional functionality can be independently modulated by changing their orientations.